Post a New Question

Trigonometry Help

posted by .

Simplify:
sin(x-y)cosy+cos(x-y)siny
= (sinxcosy-cosxsiny)cosy+(cosxcosy+sinxsiny)siny
= ???

What do I do next???


Please Help and Thank You

  • Trigonometry Help -

    expand it again
    = sinx cos^2 y - cosxsinycosy + cosxcosysiny + sinxsin^2 y
    = sinx(cos^2 y - sin^2 y)
    = sinxcos(2y)

  • Trigonometry Help -

    when I substitue the x's and y's I get different answers.

    do I need brackets on (sinxcosy-cosxsiny) and (cosxcosy+sinxsiny)?

    could the next step be: sinxcosy-cosxsinycosy+cosxcosy+sinxsinysiny without the brackets? or would that be wrong?

  • correction - Trigonometry Help -

    found my error
    2nd last line should have been

    = sinx(cos^2 y + sin^2 y)
    = sinx (1)
    = sinx

  • Trigonometry Help -

    thank you so much=)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question